Non-destructive biomarkers can reveal effects of the association of microplastics and pharmaceuticals or personal care products. (April 2022) - da Silva, Letícia Fernanda; Nobre, Caio Rodrigues; Moreno, Beatriz Barbosa; Pereira, Camilo Dias Seabra; de Souza Abessa, Denis Moledo; Choueri, Rodrigo Brasil; Gusso-Choueri, Paloma Kachel; Cesar, Augusto
Abstract: Methods to assess the effects of contaminants on marine organisms typically involve euthanasia to obtain samples, but less invasive techniques may be more appropriate for working with threatened species. In this study, were assessed the biological responses of crabs exposed to microplastics and contaminants of emerging concern. Biochemical and cellular effects (lipid peroxidation, DNA damage, cholinesterase activity, and lysosomal membrane stability) in hemolymph were analyzed in a kinetic study, at 3 and 7 days, in U. cordatus exposed to microplastics spiked with Triclosan (TCS) or 17α-Ethynylestradiol (EE2). The results showed that the contaminants were produced toxic effects in the crabs exposed either to the microplastics alone (oxidative stress, genotoxicity, and neurotoxicity), or to microplastics with TCS or EE2 adsorbed (neurotoxic and cytotoxic). The present study showed the responsiveness of non-lethal analyzes to understanding the biological effects of combined exposure to microplastics and chemical pollution. Graphical abstract: Unlabelled Image Highlights: Microplastics and PPCPs effects in crabs were evaluated through hemolymph samples. Non-lethal biomarkers embrace better bioethical aspects of endangered species. Virgin microplastic caused oxidative stress, genotoxicity and neurotoxicity. Microplastics carrying antibacterial and hormone were neurotoxic and cytotoxic. Our results contribute to the understanding of pollution effects through non-lethal analyses